Cigarette smoke condensate attenuates phorbol ester-mediated neutrophil extracellular trap formation - Bokaba, Refilwe Philadelphia (Afr Health Sci, 2017)
BACKGROUND: Neutrophil extracellular traps (NETs) constitute a network of chromatin fibres containing histone and antimicrobial peptides that are released by activated neutrophils. NETs protect the host against infection by trapping and facilitating phagocytosis of potentially harmful pathogens. OBJECTIVES: The aim of the current study was to investigate the effects of cigarette smoke condensate (CSC) on phorbol-ester (PMA)-mediated NETosis in vitro. METHODS: Isolated human blood neutrophils were exposed to PMA (6.25 ng/ml) in the presence or absence of CSC (40–80 µg/ml) for 90 min at 37oC. NET formation was measured using a spectrofluorimetric procedure to detect extracellular DNA and fluorescence microscopy was used to visualize nets. Oxygen consumption by PMA-activated neutrophils was measured using an oxygen sensitive electrode. RESULTS: Activation of neutrophils with PMA was associated with induction of NETosis that was significantly attenuated in the presence of CSC (40 and 80 µg/ml), with mean fluorescence intensities of 65% and 66% of that observed with untreated cells, respectively, and confirmed by fluorescence microscopy. The rate and magnitude of oxygen consumption by activated neutrophils pre-treated with CSC (80 µg/ml) was significantly less than that observed with untreated cells (73% of the control system), indicative of decreased production of reactive oxidants in the presence of CSC. CONCLUSION: The inhibition of NETosis observed in the presence of CSC correlated with attenuation of oxygen consumption by PMA-activated neutrophils suggesting a mechanistic relationship between these events. If operative in vivo, smoking-related attenuation of NETosis may impair host immune responses and increase the risk of respiratory infections.